The effect of ocean acidification and temperature on the fertilization and embryonic development of the Sydney rock oyster Saccostrea glomerata (Gould 1850) - Parker, L M; Ross, P M; O'Connor, W A (Global Change Biology, 2009)
This study investigated the synergistic effects of ocean acidification (caused by elevations in the partial pressure of carbon dioxide pCO2) and temperature on the fertilization and embryonic development of the economically and ecologically important Sydney rock oyster, Saccostrea glomerata (Gould 1850). As pCO2 increased, fertilization significantly decreased. The temperature of 26 °C was the optimum temperature for fertilization, as temperature increased and decreased from this optimum, fertilization decreased. There was also an effect of pCO2 and temperature on embryonic development. Generally as pCO2 increased, the percentage and size of D-veligers decreased and the percentage of D-veligers that were abnormal increased. The optimum temperature was 26 °C and embryonic development decreased at temperatures that were above and below this temperature. Abnormality of D-veligers was greatest at 1000 ppm and 18 and 30 °C (≥90%) and least at 375 ppm and 26 °C (≤4%). Finally prolonged exposure of elevated pCO2 and temperature across early developmental stages led to fewer D-veligers, more abnormality and smaller sizes in elevated CO2 environments and may lead to lethal effects at suboptimal temperatures. Embryos that were exposed to the pCO2 and temperature treatments for fertilization and embryonic development had fewer D-veligers, greater percentage of abnormality and reduced size than embryos that were exposed to the treatments for embryonic development only. Further at the elevated temperature of 30 °C and 750-1000 ppm, there was no embryonic development. The results of this study suggest that predicted changes in ocean acidification and temperature over the next century may have severe implications for the distribution and abundance of S. glomerata as well as possible implications for the reproduction and development of other marine invertebrates. © 2009 Blackwell Publishing Ltd.